FLUID GEOCHEMISTRY INVESTIGATIONS ON THE VOLCANIC SYSTEM OF METHANA - D'Alessandro, W.; Brusca, L.; Kyriakopoulos, K.; Margaritopoulos, M.; Michas, G.; Papadakis, G. (Bulletin of the Geological Society of Greece, 2007)
An extensive geochemical survey on the fluids released by the volcanic/geothermal system of Methana was undertaken. Characterization of the gases was made on the basis of the chemical and isotopie (He and C) analysis of 14 samples. CO2 soil gas concentration and fluxes were measured on the whole peninsula at more than 100 sampling sites. 31 samples of thermal and cold groundwaters were also sampled and analysed to characterize the geochemistry of aquifers. Anomalies referable to the geothermal system, besides at known thermal manifestations, were also recognized at some anomalous degassing soil site and in some cold groundwater. These anomalies were always spatially correlated to the main active tectonic system of the area. The total CO2 output of the volcanic system has been preliminary estimated in about 0.2 kg s~ . Although this value is low compared to other volcanic systems, anomalous C02 degassing at Methana may pose gas hazard problems. Such volcanic risk, although restricted to limited areas, cannot be neglected and further studies have to be undertaken for its better assessment.